Comparative Analysis of In-Situ Left Internal Mammary Artery and Saphenous Vein Composite Grafts for Left Anterior Descending Artery Revascularization: A Propensity-Matched Study - Parth Bharat Solanki; Nivedita Vadodaria; Smit Bharat Solanki; Hitendra Kanzaria (Ukrainian Journal of Cardiovascular Surgery, 2025)
Aim. This study aimed to evaluate the early and mid-term outcomes of a novel strategy using the in-situ left internal mammary artery (LIMA) with a great saphenous vein graft (SVG) to bypass the left anterior descending artery (LAD) in coronary artery bypass grafting (CABG).Materials and methods. A total of 1,240 patients were included in this retrospective observational study. Using propensity-score matching, 155 patients were assigned to the LIMA + SVG group and 155 to the LIMA − LAD group. Early mortality, postoperative complications, and mid-term major adverse cardiovascular and cerebrovascular events (MACCE) were compared between the two matched groups following the procedure.Results. No significant differences were observed in early mortality rates between the LIMA + SVG group and the LIMA − LAD group (3.2 % vs. 2.6 %, P=0.69). For mid-term outcomes, the incidence of MACCE was slightly higher in the LIMA + SVG group, but this difference was not statistically significant (14.2 % vs. 12.3 %, hazard ratio = 1.18, 95% CI, 0.38 to 6.72; P=0.73). Computed tomography coronary artery angiography (CTCA) revealed a LIMA + SVG composite graft patency rate of 93 % (72/77) at 25 months post-procedure.Conclusions. The use of in-situ LIMA with SVG to revascularize LAD was associated with comparable early and mid-term outcomes to using LIMA alone. These findings suggest that the LIMA + SVG composite graft may be a viable alternative strategy when LIMA alone cannot adequately bypass the LAD, particularly in emergency settings.